Talaromyces purpureogenus-mediated mycosynthesis of aluminium oxide nanoparticles and characterization of the physicochemical properties at different calcination temperatures - Kheirel Anuar, Muhammad Salahudin; Che Abdullah, Che Azurahanim; Nazarudin, Muhammad Farhan; Ishaq, Shamsu Ibrahim; Azmai, Mohammad Noor Amal; Salleh, Annas; Md Yasin, Ina Salwany; Yusof, Mohd Termizi (Elsevier B.V., 2025)
The study reports an environmentally friendly and simple green technique for the synthesis of aluminium oxide nanoparticles (Al2O3-NPs). The green synthesis of Al2O3-NPs using natural products has garnered significant interest due to their non-toxic, cost-effective, convenient, and eco-friendly nature. However, there is limited literature on the green synthesis of Al2O3-NPs using fungal materials and the influence of calcination temperatures on the physicochemical characteristics of mycogenic nanoparticles (NPs). To date, no studies have explored the influence of calcination temperatures on the physicochemical characteristics of mycogenic Al2O3-NPs. This study aimed to compare and characterize the mycogenic synthesis of Al2O3-NPs and investigate how three different calcination temperatures influence the structural properties of the NPs. In this study, Al2O3-NPs were synthesized using the Talaromyces purpureogenus isolate SD7 through extracellular production. To study the effects of calcination temperatures on the physicochemical properties of the NPs, the mycogenic Al2O3-NPs were calcined at temperatures ranging from 550 °C to 750 °C based on thermogravimetric analysis. The samples were further characterized using various spectroscopic and imaging techniques. The analysis of ultraviolet–visible (UV–Vis) spectrophotometer, X-ray diffraction (XRD), and high-resolution transmission electron microscopy (HR-TEM) demonstrated that particle size escalated with elevated calcination temperatures. Characterization techniques using field emission scanning electron microscopy (FESEM), HR-TEM, and XRD confirmed that the Al2O3-NPs exhibited both rod-like, spherical structures with irregular sizes, and showed the presence of nanocrystalline γ-Al2O3. However, only the sample calcined at 550 °C remains within the nanoscale range, whereas samples treated at higher temperatures show considerable grain growth, exceeding the nanometer scale. This study showcases the potential of mycosynthesized Al2O3-NPs using fungal material as an eco-friendly alternative. It also emphasizes the significant influence of calcination temperatures on the structural and physicochemical properties of mycogenic Al2O3-NPs, underscoring their suitability for a wide range of applications.